DISEMINASI EDUKASI PERTANIAN DI YOUTUBE: ANALISIS NETNOGRAFI RESEPSI AUDIENS PADA KANAL PENYULUH PERTANIAN LAPANGAN - Kuntoro, Diadji; Muslikhah, Febri Palupi (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This study analyzes audience reception of digital agricultural extension messages delivered through the Penyuluh Pertanian Lapangan YouTube channel. The transition from face-to-face agricultural extension to digital platforms signifies a major shift in how farmers access and apply agricultural knowledge. Using Stuart Hall’s (1980) encoding/decoding reception model and a qualitative netnographic approach, this research examined 240 audience comments on selected videos to identify recurring meanings and patterns of response. Findings reveal that most audiences demonstrate dominant-hegemonic readings, fully accepting the messages as credible and practical sources of agricultural information. Others show negotiated readings by adapting the messages to their local farming contexts, while oppositional readings appear in critiques of technical language and presentation style. Six main themes emerged: educational appreciation, communication style, validation of field practice, social contextualization, critique of terminology, and religious expressions. Factors shaping audience reception include farming experience, digital literacy, educational background, geographical context, and perceived credibility of the instructor. This study concludes that YouTube-based agricultural extension fosters participatory learning that strengthens knowledge transfer and farmer empowerment. Theoretically, it extends audience reception studies into digital agricultural communication, while practically, it offers insight for developing participatory and context-sensitive communication strategies in digital extension programs.